1996
DOI: 10.1002/etc.5620150612
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical detection of lead in plant tissues

Abstract: Abstract-A histochemical staining technique using sodium rhodizonate was developed for detecting lead in living or preserved plant tissues. Sodium rhodizonate formed a bright scarlet-red precipitate with lead at pH 3.0, but showed no significant color responses with other metals. The precipitation of lead by this staining technique was confirmed by detection of lead in the red-stained precipitate with electron microscopy X-ray analysis. This histochemical technique for lead provided rapid, quantifiable, and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Wierzbicka and Antosiewicz (1993) reported that in the roots Pb is binding to cell walls and vacuoles, or by extracellular precipitation (Verma and Dubey, 2003), which prevents it from entering the cytoplasm, avoiding the toxic effects of Pb on the cytosol. Thus, cell walls can be considered as barriers to symplastic and apoplastic lead transport (Tung and Temple, 1996). The exclusor behavior of oleander under controlled conditions confirms the results obtained in the field.…”
Section: Discussionsupporting
confidence: 72%
“…Wierzbicka and Antosiewicz (1993) reported that in the roots Pb is binding to cell walls and vacuoles, or by extracellular precipitation (Verma and Dubey, 2003), which prevents it from entering the cytoplasm, avoiding the toxic effects of Pb on the cytosol. Thus, cell walls can be considered as barriers to symplastic and apoplastic lead transport (Tung and Temple, 1996). The exclusor behavior of oleander under controlled conditions confirms the results obtained in the field.…”
Section: Discussionsupporting
confidence: 72%
“…Cadmium, taken up by the roots, accumulates preferentially in the trichomes on the leaf surface of Indian mustard (Salt et al 1995b), suggesting that Cd storage in the trichome is a detoxi®-cation mechanism. Trichomes in other plants have been reported to accumulate toxic ions, including Mn (Blamey et al 1986) and Pb (Martell 1974;Tung and Temple 1996), or to regulate Ca storage and its release (De Silva et al 1996). Expression of a type-2 metallothionein, a metal-binding protein, in trichomes of bean plants has been suggested to be a mechanism for heavy-metal tolerance (Foley and Singh 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Lead can be identified by optical microscopy, e.g., by rhodizonic acid that forms red complexes with this metal (Tung and Temple 1996). Cadmium may be identified, e.g., by Leadmium reagent (Xiong et al 2009) in fluorescence and confocal microscopy.…”
Section: Detection Of Tms In Plant Cell Wallmentioning
confidence: 99%